Targeting Microglia to Treat Degenerative Eye Diseases - Wang, Sean K.; Cepko, Constance L. (Frontiers in Immunology, 2022)
Microglia have been implicated in many degenerative eye disorders, including retinitis pigmentosa, age-related macular degeneration, glaucoma, diabetic retinopathy, uveitis, and retinal detachment. While the exact roles of microglia in these conditions are still being discovered, evidence from animal models suggests that they can modulate the course of disease. In this review, we highlight current strategies to target microglia in the eye and their potential as treatments for both rare and common ocular disorders. These approaches include depleting microglia with chemicals or radiation, reprogramming microglia using homeostatic signals or other small molecules, and inhibiting the downstream effects of microglia such as by blocking cytokine activity or phagocytosis. Finally, we describe areas of future research needed to fully exploit the therapeutic value of microglia in eye diseases.